Photon and Particle Impact Spectroscopy and Dynamics of Atoms, Molecules, and Clusters (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
There have been three recent developments in AMO and cluster science: a) new and progressively precise technologies to synthesize materials with good purity statistics for their gas-phase, as thin films, or in their liquid-phase; b) significant diversification of pump–probe laser and particle sources and related experimental techniques allowing us to access both the energy response and temporal response of the target materials in ultrafast time scales; and c) increasing the availability of high-performance computer software on ever faster computers, which can be processed in both series and parallel mode. These developments have empowered the broader AMO community to address more detailed and critical aspects of the response and relaxation processes. As a result, many groups have become involved in ever-more challenging and complex investigations, pushing the frontier of knowledge. This Special Issue will provide a forum in which to broadcast emerging research results, creating a repository professional knowledge, novel research questions and outlooks, and stimulating brand-new collaborations.